User performance on laptops vs. tablets: an experiment in the field. Issue 13 (3rd October 2022) - Liberatore, Matthew J.; Wagner, William P.
ABSTRACT: This research presents the results of a field experiment that measured users' performance, satisfaction and confidence in completing a number of different Business Intelligence (BI) tasks using tablets and compares the results with those obtained with laptops. Previous usability research for tablets addressed basic, elemental, non-complex tasks. This study takes advantage of improvements in technology that make it feasible to conduct experiments with actual business users performing complex tasks at their corporate sites using a mobile lab. The motivation for conducting the field study was to determine the task-technology fit for tablets when completing complex business tasks. Previous task-technology fit research employed the use of surveys and/or interviews to collect data regarding the perceived fit of a specific technology to a task. The perceived fit was then seen to affect performance. Since we obtained experimental task performance and user satisfaction data, the data itself can be used to assess fit. This research shows that users working on laptops perform better than users with tablets for completing a variety of BI tasks.